Association between autonomic nervous dysfunction and cellular inflammation in end-stage renal disease. Issue 1 (December 2016) - Seibert, Eric; Zohles, Kristina; Ulrich, Christof; Kluttig, Alexander; Nuding, Sebastian; Kors, Jan; Swenne, Cees; Werdan, Karl; Fiedler, Roman; Girndt, Matthias
Abstract Background Alterations in autonomic nervous function are common in hemodialysis (HD) patients. Sympathetic as well as parasympathetic activation may be associated with immune and inflammatory responses. We intended to confirm a role of autonomous dysregulation for inflammation in HD patients. Methods 30 HD patients (including 15 diabetics) and 15 healthy controls were studied for heart rate variability (HRV) using 5 min ECG recordings. Heart rate variability was estimated by time-domain parameters (the standard deviation of the RR intervals (SDNN) and the percentage of pairs of adjacent RR intervals differing by >50 ms (pNN50)) and frequency-domain-analysis (high- and low-frequency variation of RR intervals, HF and LF). Inflammation was detected as serum C-reactive Protein (CRP), IL-6 and circulating monocyte subpopulation numbers. Immune cells were characterized by ACh receptor expression. Results Patients differed from controls in terms of age (68.0 [14.8] yrs vs. 58.0 [13.0] yrs, p  < 0.001; Median [IQR]) and sex. However, HRV parameters were different in controls and HD patients (SDNN controls 34.0 [14.0] ms, HD patients 15.5 [14.8] ms, p  < 0.01). This finding was not restricted to patients with diabetes mellitus (diab), although diabetes is an important cause of autonomous dysfunction (SDNN, diab 13.0 [14.0] ms, non-diab 18.0 [15.3] ms, p  = 0.8). LF and HF were reduced by the same magnitude to 1/3 of those in controls. Patients suffered from chronic inflammation (CRP 9.4 [12.9] mg/l, controls 1.6 [2.4] mg/l, p  < 0.001) and expanded proinflammatory monocyte subpopulations (CD14++/CD16+ cells: patients 41 [27]/μl, controls 24 [18]/μl, p  < 0.01). ECG parameters did not correlate with inflammation in patients, but monocyte ACh receptor expression was enhanced, indicating potentially elevated responsiveness of this cell type to parasympathetic regulation. Conclusions HD patients have strongly impaired HRV. Chronic inflammation is not related to autonomous dysfunction, although monocytes express the ACh receptor at enhanced density making them potentially more sensitive to parasympathetic effects. Trial registration This study was listed with ClinicalTrials.gov (NCT00878033 ).